Rationality of Time-Dependent Antimicrobial Use in Intensive Care Units in China: A Nationwide Cross-Sectional Survey - Liu, Jiao; Zhang, Sheng; Huang, Sisi; Chen, Yizhu; Zhang, Lidi; Du, Hangxiang; Wang, Tao; Liu, Yongan; Xu, Yan; Chen, Dechang (Frontiers in Medicine, 2021)
Background: Extended/continuous infusion and therapeutic drug monitoring (TDM) of time-dependent antimicrobials are recommended for optimizing drug exposure for patients in intensive care units (ICUs), although practical application of these measures remains uncertain. We surveyed current practices in infusion and monitoring of commonly prescribed time-dependent antimicrobials in ICUs across China. Methods: From December 2019 to January 2020, we sent online questionnaires about various aspects of infusion and monitoring of time-dependent antimicrobials to intensivists across China. Responses from clinicians were matched with their professional titles using the Sankey diagram. Univariate and multivariate logistic regression analyses were performed to find factors associated with TDM. Results: A total of 3687 ICU specialists from 31 provincial administrative regions of China responded to our questionnaires. Antibiotic stewardship (ABS) teams were available in hospitals as reported by 3243 (88.0%) intensivists, including 1308 (35.5%) who were ABS team members. Although most intensivists (3490, 94.7%) were acquainted with the concept of prolonged/continuous infusion, nearly half of them (1634, 44.3%) commonly administered β-lactam antibiotics intermittently. Nearly two-thirds of the respondents reported that their hospitals could not perform TDM. Our multivariable logistic regression analysis revealed that at the hospital level, knowledge of drug sample timing and attitude toward monitoring treatment effects and drug trough or peak concentration influenced the decision to conduct TDM. Conclusions: We found great variability in prescribing practices, from drug administration to TDM, for several time-dependent antibiotics commonly used for patients with severe infections. Further studies are necessary to effectively evaluate strategies to promote consistent prescribing behavior.